Predictors associated with studies and lifestyle and subjective feeling of depressive symptoms among Polish medical students - Łukasz Bryliński; Agata Bura; Piotr Duda; Paulina Drożak; Katarzyna Augustowska; Martyna Drożak (Kazimierz Wielki University, 2020)
Introduction and objective. Depression is a disorder that medical students are subjected to. The aim of the research was to investigate the occurrence of subjective feeling of depressive symptoms among Polish medical students during the course of medical studies and to determine predictors of this phenomenon that are associated with studies and lifestyle. Material and method. The research tool was author's questionnaire. 1023 medical students from each year of medical education and different Polish universities took part in the study. Results. 52.79% of the respondents had noticed symptoms that might had pointed to depression during the course of their medical studies. The research suggests that predictors of subjective feeling of depressive symptoms among medical students are: repeating a university subject, repeating a year in university, low self-assessment of academic performance during studying, considering dropping out of university, low satisfaction from the choice of studying medicine, reaching for alcohol in order to de-stress or discharge negative emotions, not having interests that enable to relax, not doing sports regularly, not participating in social gatherings often enough, not sleeping enough, having problems with maintaining stable body weight and not being religious. Conclusions. There are many lifestyle and studies connected factors associated with depressive symptoms among Polish medical students. The study suggests that it is important for students and their communities to pay attention to the emergence of them in order to improve the well-being of students.